1999
DOI: 10.1034/j.1399-3054.1999.106312.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue browning of in vitro cultures of Scots pine: Role of peroxidase and polyphenol oxidase

Abstract: Callus cultures from shoot tips of mature Scots pine (Pinus sylvestris L.) were characterized by rapid browning and an inability to regenerate. The peroxidase (POD) and polyphenol oxidase (PPO) activities and relationship to browning in such cultures were compared with embryogenic and non‐embryogenic cultures of Scots pine, started from immature embryos of three different pine clones. The browning in callus cultures derived from pine buds was visible approximately after 2 weeks of culture, and continued therea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 34 publications
(45 reference statements)
3
41
1
5
Order By: Relevance
“…In this sense, browning hampers the establishment of tissue culture in Aloe (Abrie and van Staden, 2001), Dioscorea alata (Bhat and Chandel, 1991), Musa spp. (Titov et al 2006) and Pinus sylvestris (Laukkanen et al 1999). Moreover, some plant growth regulators such as BAP, kinetin, TDZ, IAA alone or in combination with 2,4-D were reported to increase browning in Aloe species (Natali et al 1990;Meyer and van Staden, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, browning hampers the establishment of tissue culture in Aloe (Abrie and van Staden, 2001), Dioscorea alata (Bhat and Chandel, 1991), Musa spp. (Titov et al 2006) and Pinus sylvestris (Laukkanen et al 1999). Moreover, some plant growth regulators such as BAP, kinetin, TDZ, IAA alone or in combination with 2,4-D were reported to increase browning in Aloe species (Natali et al 1990;Meyer and van Staden, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Browning is caused by the oxidation of phenolic compounds, released from the cut ends of the explants, by polyphenoloxidases, peroxidases or air (Bhat and Chandel, 1991;Laukkanen et al 1999). In this sense, browning hampers the establishment of tissue culture in Aloe (Abrie and van Staden, 2001), Dioscorea alata (Bhat and Chandel, 1991), Musa spp.…”
Section: Discussionmentioning
confidence: 99%
“…[34,35] showed that accumulation of these compounds leads to browning and possibly death of the explants. Moreover, oxidized phenolic compounds may inhibit enzyme activity and result in the darkening of the culture medium and subsequent lethal browning of explants [36,37]. Thus, the study revealed that for successful control of oxidative lethal browning the concentration of antioxidant ascorbic acid is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the increased content of total phenolic compounds in tetraploid origin calluses resulted in the loss of their organogenic potential. Phenolic compounds, especially oxidized phenolics, may contribute to the inhibition of enzymatic activities, resulting in the darkening of the culture medium and subsequent lethal browning of explants [32,33]. It has been reported that oxidized phenolics generally affect in vitro proliferation and regeneration negatively [34].…”
mentioning
confidence: 99%